Designing an Information System to Support Implementation of The Retrieval Practice Method - Witarto Adi Winoto; Irvania Sukma Kumala (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
The Retrieval Practice method was developed based on a memory model. In this study, the characteristics of deep rehearsal, including semantic processing accompanied by pictures are the basis for making quiz questions. The application of the Retrieval Practice method requires the support of Information Systems. Focus Group Discussions discuss aspects of repetition in learning. The aim of supporting the application of the Retrieval Practice method is expected to be able to improve student competencies, especially in terms of maturing students' knowledge and understanding. Data is measured from testing semester 2-2018 and semester 1-2019. Conclusion: Cognitive understanding for teachers will help students understand knowledge, understanding, analysis and synthesis into their memories. Metode Retrieval Practice dikembangkan berdasarkan model memori. Dalam penelitian ini, karakteristik deep rehearsal, termasuk pemrosesan semantik yang disertai gambar adalah dasar untuk membuat pertanyaan kuis. Penerapan metode Retrieval Practice memerlukan dukungan Sistem Informasi. Diskusi Kelompok Terfokus membahas aspek pengulangan dalam pembelajaran. Tujuan mendukung penerapan metode Retrieval Practice ini diharapkan dapat meningkatkan kompetensi mahasiswa terutama dalam hal mematangkan pengetahuan dan pemahaman para mahasiswa. Data diukur dari pengujian semester 2-2018 dan Semester 1-2019. Kesimpulan : pemahaman kognitif bagi dosen akan membantu mahasiswa memahami pengetahuan, pemahaman, analisis dan sintesis ke dalam ingatan mereka.